2019
DOI: 10.1371/journal.ppat.1008180
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-defensin 5 differentially modulates adenovirus vaccine vectors from different serotypes in vivo

Abstract: Adenoviral vectors have shown significant promise as vaccine delivery vectors due to their ability to elicit both innate and adaptive immune responses. α-defensins are effector molecules of the innate immune response and have been shown to modulate natural infection with adenoviruses, but the majority of α-defensin-adenovirus interactions studied to date have only been analyzed in vitro. In this study, we evaluated the role of α-defensin 5 (HD5) in modulating adenovirus vaccine immunogenicity using various ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…However, we were unable to account for the extensive HD5 binding to the hexons of HAdV-5 in our cryoEM studies [ 9 ]. Our new results indicate that the HVR1 loop of hexon functions in cooperation with the vertex proteins as a previously unidentified determinant of HD5-mediated neutralization, which is further supported by the recent demonstration of neutralization and enhancement of HAdV-based vectors by HD5 in a mouse model [ 37 ]. If either HVR1 or both vertex determinants (four residues near the N-terminus of fiber and the C-terminal half of PB) are derived from a resistant serotype, then neutralization does not occur.…”
Section: Discussionsupporting
confidence: 79%
“…However, we were unable to account for the extensive HD5 binding to the hexons of HAdV-5 in our cryoEM studies [ 9 ]. Our new results indicate that the HVR1 loop of hexon functions in cooperation with the vertex proteins as a previously unidentified determinant of HD5-mediated neutralization, which is further supported by the recent demonstration of neutralization and enhancement of HAdV-based vectors by HD5 in a mouse model [ 37 ]. If either HVR1 or both vertex determinants (four residues near the N-terminus of fiber and the C-terminal half of PB) are derived from a resistant serotype, then neutralization does not occur.…”
Section: Discussionsupporting
confidence: 79%
“…A similar mechanism has been shown in shigella, another gastrointestinal pathogen that appropriates HD5 to facilitate infection [19, 20]. In addition, only viruses containing hexons in which all of the HVRs are from one serotype are enhanced, including a recently published HAdV-5 chimera containing all of the HVRs of HAdV-48 hexon [32]. This suggests that homotypic interactions involving hexon HVRs mediate enhancement.…”
Section: Discussionmentioning
confidence: 63%
“…Importantly, all three HAdV capsid proteins play a role in neutralization, but hexon rather than PB or fiber determines enhancement. Thus, we have extensively revised the prior model of HD5-mediated neutralization and established the feasibility of this process to shape viral evolution in vivo , which is further supported by the recent demonstration of neutralization and enhancement of HAdV-based vectors by HD5 in a mouse model [32].…”
Section: Discussionmentioning
confidence: 92%
“…Upon searching for the natural mechanisms that may neutralize adenoviruses, it was found that human alpha defensin 5 (HD5), a small antimicrobial peptide, has potent inhibitory activity against species C adenovirus HAdV-C5 [ 93 ]. However, HD5 does not inhibit adenoviruses of species D and F, but rather augments the virus infection in vitro and increases adaptive responses to the virus-encoded transgene antigens in vivo [ 94 ]. Furthermore, pre-treatment of mice with HD5 prior to HAdV-D26 injection resulted in a higher cytokine response than to the virus alone.…”
Section: Factors Modulating Cytokine and Chemokine Production In Resp...mentioning
confidence: 99%
“…Mechanistically, more robust cytokine production in response to the virus–HD5 complexes is thought to be due to more efficient virus entry into dendritic cells in the presence of HD5. It is plausible that HD5 functions as a polycation, and upon binding to adenovirus, it shields the negatively charged amino acids present at the surface of the virion, thus reducing repulsion between the negatively charged virus surface and plasma membrane, leading to a more efficient infection of dendritic cells [ 94 ].…”
Section: Factors Modulating Cytokine and Chemokine Production In Resp...mentioning
confidence: 99%